2021
DOI: 10.1039/d1ta04467b
|View full text |Cite
|
Sign up to set email alerts
|

Nanosupercapacitors with fractal structures: searching designs to push the limit

Abstract: Microsupercapacitors (MSCs) are of increasing interest for powering microelectronic systems, while their applications are still limited by insufficient energy densities due to relatively large sizes. To address this critical challenge,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Importantly, fractal microelectrode configuration was also valid to enhance the performance by maximizing the electrode material utilization [101,106,107]. Therefore, several kinds of fractal NSCs were fabricated based on space-filling curves of different iterated orders by the same FIB method [22]. It is demonstrated that the fractal NSCs exhibited marked enhancement of capacitances compared with interdigital NSCs, attributed to the stronger electric field intensity coming from the abundant corners of fractal designs, testified by COMSOL simulations (Fig.…”
Section: Focused Ion Beammentioning
confidence: 91%
See 2 more Smart Citations
“…Importantly, fractal microelectrode configuration was also valid to enhance the performance by maximizing the electrode material utilization [101,106,107]. Therefore, several kinds of fractal NSCs were fabricated based on space-filling curves of different iterated orders by the same FIB method [22]. It is demonstrated that the fractal NSCs exhibited marked enhancement of capacitances compared with interdigital NSCs, attributed to the stronger electric field intensity coming from the abundant corners of fractal designs, testified by COMSOL simulations (Fig.…”
Section: Focused Ion Beammentioning
confidence: 91%
“…FIB technology is an integral part of micro/nano-fabrication technology and semiconductor integrated circuit, which can achieve sub-micrometer resolution patterns in a mask-free process by selective ablating and removing material or inducing chemical reactions of target films [18,19,21,22,31,105]. Majumder's group prepared graphene-based MSCs by converting the directly written GO film into precise rGO pattern using FIB technology [18].…”
Section: Focused Ion Beammentioning
confidence: 99%
See 1 more Smart Citation
“…The richer sharp corners of electrodes yield the stronger electric field intensity as demonstrated by COMSOL Multiphysics simulations, thus enhancing the charge storage ability. 20 Third, the in-plane design can effectively utilize the space by making use of microelectrode gaps (or called interspaces) instead of separators required by conventional sandwich architecture. As a result, the ion-transport resistance of energy storage devices can be decreased and a high-frequency response can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the in-plane design can provide abundant sharp corners in comparison with other designs. The richer sharp corners of electrodes yield the stronger electric field intensity as demonstrated by COMSOL Multiphysics simulations, thus enhancing the charge storage ability . Third, the in-plane design can effectively utilize the space by making use of microelectrode gaps (or called interspaces) instead of separators required by conventional sandwich architecture.…”
Section: Introductionmentioning
confidence: 99%